Pengaruh Kohesivitas dan Kepuasan Kerja terhadap Organizational Citizenship Behavior di PT Agricon - Resa Dwi Larasati; Nurmala K Pandjaitan; Aji Hermawan (Jurnal Manajemen dan Organisasi, 2017)
PT Agricon is an agrochemicals organization. Hence, as an organization, it needs to have a high quality resources in order to produce a good performance. One of the signs of high quality resources is if the human resources of the organization has extra-role behavior. The extra-role expected by the organization is Organizational Citizenship Behavior (OCB). This study aims to determine the effect of cohesiveness and job satisfaction of PT Agricon’s employees to OCB. This study used convenience sampling as sample selection technique and questionnaires is distributed to 120 respondents. Structural Equation Model (SEM) analysis is used to analyze effect of cohesiveness and job satisfaction on OCB. The results show that the cohesiveness obtained by PT Agricon comes from the ATGS (Attraction to The Group Task) dimension, job satisfaction comes from the satisfaction dimension of the work itself and the OCB is comes from the civic virtue dimension. Meanwhile, the results of the analysis shows that cohesiveness and job satisfaction give positive effect on OCB at PT Agricon.